A Proposed Model To Improve Public Participation Towards Renewable Energy Development (PPRED) In Malaysia Through Validation Study - Wan Nur Rahini Aznie Zainudin; Wan Muhammad Zainuddin Wan Abdullah (FLE Learning Ltd trading, 2024)
The purpose of this study is to validate on the dimensionality of the instruments of Public Participation towards Renewable Energy Development (PPRED) using validation study. These instruments include willingness to pay on energy generated from RE, public awareness on RE, degree of knowledge on RE, willingness to adopt RE technology, environmental concern and attitude towards RE usage. Using a survey of 172 respondents, an exploratory factor analysis (EFA) was used to assess the factor structure, confirmatory factor analysis (CFA) was used to test unidimensionality of measurement model, the items discriminant and convergence was measured using correlation and Cronbachs Alpha was applied to establish the internal consistency of reliability between items. EFA extracted six variables as proposed by literatures, while under CFA, model unidimensionality, discriminant and convergence validity and internal consistency of reliability were achieved. However, validated instruments may vary depending on development and acceptance of RE in a particular country.